Epidemiologic study about Chagas disease in Amapá State Brazil in the years 2016 at 2021 (Research, Society and Development, 2022)
Chagas disease (CD) is a neglected tropical disease of high morbidity and mortality. Despite the great reduction in the incidence of acute chagas disease (DCA) cases, the occurrence of these cases may be related to oral transmission by the ingestion of contaminated food, especially in the Amazon region, which over the last few years has been gaining prominence. Through tabulation of data contained in SINAN - Notifiable Diseases Information System - by socio-demographic profile, transmission mode and notifications made in the period from 2016 to 2021. The aim of this research was to trace a profile of disease behavior in the state of Amapá and thus guide control activities. The analysis showed that all age groups and races can be affected by the disease and that surveillance and control actions should be intensified mainly for the oral form of transmission, aiming at a decrease in the occurrence in the coming years, since it is a disease that affects hundreds of people in the state over the years.